Out of nowhere : a novel - Sebestyen, Ouida (New York : Orchard Books, 1994)
When he no longer fits into his vagabond mother's life, thirteen-year-old Harley adopts an abandoned dog and falls in with an outspoken old woman, a cantakerous junk collector, and an energetic and loving teenage girl.
"A Melanie Kroupa book"--Half t.p.
5-8.
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction; Mothers and sons -- Fiction; Foster home care -- Fiction; Dogs -- Fiction; Mothers and sons -- Fiction; Foster home care -- Fiction